Analisis Strategi Pembelajaran Bahasa Arab Dasar Nonformal Untuk Meningkatkan Minat Belajar Penyintas Bencana Banjir Bandang di Kelurahan Kappuna Kecamatan Masamba Kabupaten Luwu Utara - Nur Fadillah; Mahlani Sabae; Muhammad Ibrahim (Universitas Muhammadiyah Makassar, 2021)
The objectives of this study are 1. To determine the analysis of non-formal basic Arabic learning strategies to increase learning interest in flash flood survivors in Kappuna village, Masamba sub-district, North Luwu district. 2. To find out the supporting and inhibiting factors in increasing the interest in learning of flash flood survivors in Kappuna Village, Masamba District, North Luwu Regency. 3. To find out the efforts to increase the interest in learning of flash flood survivors in Kappuna Village, Masamba District, North Luwu RegencyThe results showed that the non-formal basic Arabic learning strategy that was applied to increase the interest in learning of banjir bandang survivors was a mufrodat learning strategy which was then combined with the direct learning method (الطريقة المباشرة). Interest is influenced by several supporting factors including volunteers, availability of writing instruments, family and environment and interesting materials. The inhibiting factors are the sense of trauma, inadequate facilities and infrastructure and the distance to the place of learning which is quite difficult to reach for the survivors. Then behind these factors, there are efforts made by several parties including involving volunteers from several regions to take a psychosocial approach to child survivors.